The Effect of Acetic Acid Concentration on the Physicochemical Properties of Shrimp Shell Powder (Fenneropenaeus Merguiensis de Man): Shrimp shell powder - Saputra, David Deni; Mursyid, Mursyid (Jurnal Bio-Geo Material Dan Energi, 2023)
Sea waters in Indonesia are rich with various types of invertebrates, one of which is shrimp. Jerbung shrimp is one type of shrimp that is abundant in the market in the city of Jambi, shrimp can be processed into several processed products such as frozen shrimp, dried shrimp, canned shrimp, and others. In Indonesia, shrimp undergo a cold storage process where the head, tail, and skin are disposed of as waste. shrimp shell contains 42.23% protein; crude fiber 19.87%; fat 2.89%; calcium 13.23%; phosphorus 2.08%; and 9.56% chitin content; so that the shrimp shell has the potential to be processed into shrimp shell flour which can be further utilized as a biomaterial for the manufacture of bioplastics and biocoagulants. The purpose of this study was to determine the effect of acetic acid concentration on the physical and chemical properties of shrimp shell powder and to determine the concentration of acetic acid that produced the best physical and chemical properties. This study was conducted using a completely randomized design (CRD), including 5 concentrations of acetic acid (1%, 2.5%, 5%, 7.5%, and 10%) with 4 replications to obtain 20 experimental units. Test parameters include water content, protein content. Fat content, ash content, viscosity and color. The best treatment was shrimp shell powder soaked using 5% acetic acid solution concentration with 6.09% water content, 49.15% protein content, 0.75% fat content, 9.82% ash content, Â viscosity 69.50 Pa.s and color (L*72.75 a*0.75 b*22.50). Â The concentration of acetic acid had no significant effect on water content and color of the shrimp powder but it had a significant effect on protein, fat, and ash content as well as viscosity.